Impact of the invasive plant, Lantana camara, on bird assemblages at Male Mahadeshwara Reserve Forest, South India - Aravind, N.A.; Rao,D.; Ganeshaiah, K.N.; Shaanker, R.U.; Poulsen, J.G. (2010)
Lantana camara is an invasive species that is widespread in India. Using birds as an indicator taxon, we investigated whether Lantana invasion was correlated with changes in ecosystem health of the moist and dry deciduous forests at the Male Madeshwara Hills, Karnataka. We studied Lantana at four densities, low, medium, and high, and a no-Lantana control. Bird species diversity, species richness, and abundance were lower at high densities of Lantana in both forest types. Evenness increased with increase in Lantana density. To better understand the observed changes in bird community composition; we segregated birds into 2 guild types: microhabitat guilds and foraging guilds. An increase in Lantana density vas correlated with a decline in canopy birds (of the canopy microhabitat guilds) and insectivores (of the insectivore foraging guilds). Our results suggest that Lantana affects the structure of the bird community by decreasing diversity, and that Lantana affects certain guilds more than others.